Bioassay-Guided Isolation and in Silico Study of Antibacterial Compounds From Petroleum Ether Extract of Peperomia blanda (Jacq.) Kunth - Al-Madhagi W.M.; Hashim N.M.; Awadh Ali N.A.; Taha H.; Alhadi A.A.; Abdullah A.A.; Sharhan O.; Othman R. (American Chemical Society, 2023)
Binding energy; Ethers; Gasoline; Liquid chromatography; Mass spectrometry; Microorganisms; Molecular dynamics; Uranium metallography; Vanadium metallography; Anti-microbial activity; Antibacterial compounds; Chromatographic techniques; Methylthioadenosine phosphorylase; Minimum inhibitory concentration; Molecular dynamics simulations; Petroleum ether extract; Two Dimensional (2 D); Gas chromatography; antiinfective agent; petroleum; plant extract; bacterial infection; bacterium; chemistry; drug effect; human; isolation and purification; microbial sensitivity test; molecular model; Peperomia; Anti-Bacterial Agents; Bacteria; Bacterial Infections; Humans; Microbial Sensitivity Tests; Models, Molecular; Peperomia; Petroleum; Plant Extracts